Financial service outreach correlates Managerial competence and risk-taking behaviour - Korutaro Nkundabanyanga, Stephen; Opiso, Julius; Balunywa, Waswa; Nabeeta Nkote, Isaac (International Journal of Social Economics, 2015)
The purpose of this paper is to establish the relationship between managerial competence, managerial risk-taking behaviour and financial service outreach of microfinance institutions (MFIs). Design/methodology/approach – In this cross-sectional and correlational study, the authors surveyed 52 branches of MFIs from a population of 60 branches of 20 MFIs in eastern Uganda. Two respondents, a branch manager and a senior loan officer, were the units of enquiry for each branch. The authors put forward and tested four hypotheses relating to the significance of the relationship between perceived managerial competence, risk-taking behaviour and financial service outreach using SPSS version 20. The authors established the hypothesized relationships using Pearson correlation coefficients and obtain a mediating effect of risk-taking behaviour using partial corrections and regression analysis. Findings – The results suggest positive and significant relationships between perceived managerial competence, risk-taking behaviour and financial service outreach. However, while the direct relationship between managerial competence and financial service outreach without the mediation effect of risk-taking behaviour of managers was found to be significant, its magnitude reduces when mediation of risk-taking behaviour is allowed. Thus the entire effect does not only go through managerial competence but majorly also, through risk-taking behaviour of managers. Research limitations/implications – This study did not control for environmental factors such as laws and regulations. As such the model may have been under fitted. Nevertheless, the study has introduced a clearer understanding that outreach performance in MFIs rests with competent managers in strategic positions operating in synergy with their risk-taking behaviour. The study informs policy makers that outreach performance of the MFIs depends on the quality of the competence managers have in addition to their risk-taking propensities. Practical implications – Efforts by the stakeholders to improve financial service outreach must be matched with appropriate competences and risk-taking behaviour of managers. Originality/value – The results contribute to extant literature by investigating two explanatory variables for financial service outreach and provide initial evidence of the mediating effect of intrinsic high risk-taking behaviour of managers. Results add to the conceptual improvement in risk-taking behaviour and lend considerable support for the behavioural perspective in the study of financial service outreach of MFIs.
Keywords: Microfinance; Uganda; Managerial competence; Outreach; Risk-taking